PENERAPAN K3 LISTRIK PADA PEKERJAAN PEMASANGAN PEMBANGLIT LISTRIK TENAGA SURYA (PLTS) - Syafriyudin; Suyanto, Muhammad (LPPM IST AKPRIND Yogyakarta, 2021)
Work security is the supporting elements that support the creation of a safe workatmosphere, both material and non-material. Occupational health and safety (K3) in thebusiness world and in the industrial world must be carefully considered by all workers intheir scope of work. The implementation of K3 is one form of effort to create a workplacethat is safe, healthy, and free from environmental pollution, so it can reduce accidents atwork and increase work efficiency and productivity. Work safely from electrical hazards.Because safety is the top priority in every job. Electrical accidents occur due to carelessnessor lack of understanding of electricity. Therefore, it is necessary to pay attention to worksafety to increase readiness for electrical hazards and other potentials that may arise on thejob. Some things that need to be considered in work that uses electrical equipment, such asdeveloping an attitude of responsibility for personal safety, get used to maintainingcleanliness in the work area from material dirt, and use Personal Protection Equipment(PPE) properly and correctly. The results for three days training showed an increase inparticipants' understanding and participation of the use of the Job Safety Analysis (JSA)method and the application of K3 Electricity in carrying out work.